A new nanoclay-based bifunctional hybrid fiber membrane with hemorrhage control and wound healing for emergency self-rescue - Mei Long; Qianqian Liu; Dongyue Wang; Jie Wang; Yi Zhang; Aidong Tang; Nian Liu; Brian Bui; Wei Chen; Huaming Yang (Materials Today Advances, 2021)
The wound healing process is divided into four phases of hemostasis, inflammation, proliferation, and remodeling that each wound needs to go through to heal normally. Each phase is crucial to the healing of the wound. Herein, for the first time, we describe an emerging bifunctional hybrid fiber membrane of ZnO–Fe2O3/kaolinite nanoclay/poly-(3-caprolactone)-gelatin (ZnO–Fe2O3/Kaol/PG) that concurrently controls bleeding, prevents bacterial colonization, reduces excessive inflammation, and facilitates wound healing for the early emergency self-rescue. Topical treatment with the fiber membrane in bacteria-infected mice models could accelerate wound healing through reducing bacterial growth, and promote cell proliferation and neovascularization, which is attributed to the antibacterial and anti-inflammatory activity of ZnO–Fe2O3/Kaol. Kaolin can activate the intrinsic coagulation cascade, in addition, it can concentrate on blood platelets, RBCs, and clotting factors by absorbing fluid. Fe2O3 can facilitate RBC aggregation and clotting, while ZnO can mediate the inhibition of the release of pro-inflammatory cytokines and antibacterial effect. The fibrous architecture of PG electrostatically spun fibers can provide an appropriate environment for wound healing. Here, for the first time, we found that ZnO–Fe2O3/Kaol can control bleeding quickly for wound injury and protect the wound from external bacterial infection and reduces inflammation. The versatility and portability of the as-prepared hybrid fiber membrane make it an effective strategy for hemorrhage control and wound healing.